2011
DOI: 10.1371/journal.pone.0016412
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Steroidal Anti-Inflammatory Drugs and Prostate Cancer Risk: A Population-Based Nested Case-Control Study

Abstract: BackgroundDespite strong laboratory evidence that non-steroidal anti-inflammatory drugs (NSAIDs) could prevent prostate cancer, epidemiological studies have so far reported conflicting results. Most studies were limited by lack of information on dosage and duration of use of the different classes of NSAIDs.MethodsWe conducted a nested case-control study using data from Saskatchewan Prescription Drug Plan (SPDP) and Cancer Registry to examine the effects of dose and duration of use of five classes of NSAIDs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 40 publications
3
45
0
2
Order By: Relevance
“…Although our results are similar to those that reported aspirin amount and duration of intake (9), and other studies found no evidence of aspirin dose-effect (7, 30-33) or frequency-effect (31, 34, 35) relationship, the inability to evaluate for a dose-response relationship between aspirin/NSAID use and prostate cancer is an important limitation of this study. Second, we did not have updated data available on aspirin/NSAID use during the study.…”
Section: Discussionsupporting
confidence: 83%
“…Although our results are similar to those that reported aspirin amount and duration of intake (9), and other studies found no evidence of aspirin dose-effect (7, 30-33) or frequency-effect (31, 34, 35) relationship, the inability to evaluate for a dose-response relationship between aspirin/NSAID use and prostate cancer is an important limitation of this study. Second, we did not have updated data available on aspirin/NSAID use during the study.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have found evidence of a decreased risk of PCa for men taking aspirin, 5,6,7,8,9 whereas other studies have not found any association. 32,33 The results of our study may help explain some of these conflicting results. If aspirin reduces risk of T2E positive PCa, but not T2E negative PCa, the results of the previous studies may vary based on the T2E gene fusion status of the patients included.…”
Section: Discussionmentioning
confidence: 83%
“…Thirty-one studies (18 case–control [9-11,16,17,21-23,26,28-33,35-37] and 13 cohort [7,8,12-15,18-20,24,25,27,34]) addressed the use of any NSAID and its association with PCa incidence risk (Table 1); eight studies (two case–control [41,44] and six cohort [39,40,42,43,45,46]) investigated whether NSAID use was associated with PCa-specific mortality (Table 2). For NSAID use and PCa incidence risk, the publication dates of the studies ranged between 1989 and 2014.…”
Section: Resultsmentioning
confidence: 99%